IMPLEMENTASI KEBIJAKAN PENDIDIKAN NASIONAL - Fitri Nurpita; Mely Cahyani; Thufeil Abyan Ahmad; Muhammad Syaifuddin (Jurnal Ilmu Pendidikan Islam, 2026)
Education plays a strategic role in national development because it improves the quality of human resources. To achieve national education goals, the government establishes various policies that serve as guidelines for the implementation of education in Indonesia. However, the success of an education policy is determined not only by its formulation but also by the effectiveness of its implementation in practice. This study aims to examine the foundations of national education policy, its implementation, supporting factors, and obstacles encountered in its implementation. This study used a qualitative approach using library research. Data were obtained through a review of various literature sources, including books, scientific journal articles, previous research results, and relevant regulatory documents. The results indicate that national education policy has a strong legal, philosophical, sociological, pedagogical, and psychological foundation. Its implementation is realized through curriculum development, improving teacher quality, implementing National Education Standards, equalizing access to education, evaluating education, digitizing education, and strengthening character education. Successful implementation is supported by the role of the government, teacher professionalism, principal leadership, the availability of infrastructure, school management, community participation, and the use of technology. Obstacles still faced include disparities in educational facilities, limited human resources, funding issues, socioeconomic factors of students, and the digital divide. Therefore, synergy between all stakeholders is needed to achieve effective, equitable, and sustainable implementation of education policies.